Sistema informatizado para dispositivos móveis de coleta dos dados referentes à cesta básica do município de Botucatu/SP - Barros, Bruna Soares Xavier de [UNESP] (2012)
The collection of prices for basic goods supply is very important for the population, based on the collection and processing of these data the CLI (Cost Living Index) is calculated among others, helping consumers to shop more rationally and with a clearer view of each product impact of each product on their household budget, not only food, but also cleaning products and personal hygiene ones. Nowadays, the project of collection of prices for basic goods supply is conducted weekly in Botucatu - SP through a spreadsheet. The aim of this work was to develop a software which utilized mobile devices in the data collection and storage phase, concerning the basic goods supply in Botucatu -SP. This was created in order to eliminate the need of taking notes in paper spreadsheets, increasing efficiency and accelerating the data processing. This work utilized the world of mobile technology and development tools, through the platform".NET" - Compact Framework and programming language Visual Basic".NET" was used in the handheld phase, enabling to develop a system using techniques of object oriented programming, with higher speed and reliability in the codes writing. A HP Pavilion dv3 personal computer and an Eten glofish x500+ handheld computer were used. At the end of the software development, collection, data storing and processing in a report, the phase of in loco paper spreadsheets were eliminated and it was possible to verify that the whole process was faster, more consistent, safer, more efficient and the data were more available.